Pragmalinguistic analysis of phraseological units with the word Blick in scientific neophilological and medical texts in German - Targońska, Joanna (Papers in Linguistics, 2022)
This article is devoted to the phraseology of scientific German. It aims to analyse and describe the use of phrasemes with the component Blick in German scientific texts from a range of humanities disciplines and medical sciences. Based on corpus research, the analysis reveals which types of phrasemes with the component in question occur in medical scientific texts and which of them belong to general scientific German, occurring in texts in a variety of scientific fields. In the article, the meanings of the examined phrasemes in scientific language are provided and their pragmatic potential is discussed. In addition, the examined phrasemes are analysed in a selection of general and phraseological dictionaries and some recommendations for updating or altering lexicographic entries are provided.